COMPARATIVE ANALYSIS REGISTRATION OF NON-TRADITIONAL TRADEMARKS IN UZBEKISTAN AND SOME FOREIGN COUNTRIES (LEGISLATION AND PRACTICE REVISION) - Babakulov Zafar Kurbannazarovich (Scholar Express Journals, 2021)
In this article it will be analyze same non-traditional marks by the legislation of foreign countries.
Keywords: Trademark; non-traditional marks; personal names; TRIPS